2016
DOI: 10.1016/j.neulet.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neural discrimination of emotional speech prosody in children with autism spectrum disorder and language impairment

Abstract: Autism spectrum disorders (ASD) are characterized by deficient social and communication skills, including difficulties in perceiving speech prosody. The present study addressed processing of emotional prosodic changes (sad, scornful and commanding) in natural word stimuli in typically developed school-aged children and in children with ASD and language impairment. We found that the responses to a repetitive word were diminished in amplitude in the children with ASD, reflecting impaired speech encoding. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
1
19
1
1
Order By: Relevance
“…Consistent with this hypothesis, Boddaert and colleagues found that listening to complex synthetic speech-like stimuli can elicit abnormal cortical processing in children with autism in a similar fashion as to speech stimuli [46]. Taken together, the evidence to date suggests atypical processing of prosody and emotional prosodic cues in speech [13, 27] and deficient processing of vocal sounds, both speech and non-speech, in children with ASD [28]. By demonstrating atypical lateralization of the speech mismatch effect, the current results support the conclusions from a recent ERP study suggesting that atypicalities in responses to speech versus non-speech sounds might be related to the delayed maturation of vocal sound processing, either speech or non-speech [28], most likely due to the social nature of the stimuli.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Consistent with this hypothesis, Boddaert and colleagues found that listening to complex synthetic speech-like stimuli can elicit abnormal cortical processing in children with autism in a similar fashion as to speech stimuli [46]. Taken together, the evidence to date suggests atypical processing of prosody and emotional prosodic cues in speech [13, 27] and deficient processing of vocal sounds, both speech and non-speech, in children with ASD [28]. By demonstrating atypical lateralization of the speech mismatch effect, the current results support the conclusions from a recent ERP study suggesting that atypicalities in responses to speech versus non-speech sounds might be related to the delayed maturation of vocal sound processing, either speech or non-speech [28], most likely due to the social nature of the stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…Based upon previous findings [11, 13, 22]; see also [25]for a review), we predicted between-group differences in the responses to speech and non-speech sounds; these would be reflected in ERP components associated with early cognitive processing of speech (e.g., 300 ms post-stimulus), associated with the recognition and classification of auditory stimuli [21, 25, 26]. Due to the nature of the paired repetition ERP paradigm employed here, we expected between group differences in speech processing to be reflected in responses to the Speech Mismatch versus Speech Match trials (Speech Mismatch effect), as well as in responses to Nonspeech Mismatch versus Nonspeech Match trials (Nonspeech mismatch effect).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Significant differences in brain response (by use of ERPs) between children with and without ASD processing emotional prosodic changes in natural word stimuli have been found [52]. Eigsti, et al reported significant differences in neural activation (by use of fMRI) between adolescents with and without ASD processing affective and grammatical prosody stimuli [53].…”
Section: Limitationsmentioning
confidence: 99%